Value Engineering Analysis of Architectural Works in Construction Projects (Case Study of Citra Arafiq Serang Hospital Development) - Maddeppungeng, Andi; Asyiah, Siti; Intari, Dwi Esti; Setiawati, Dwi Novi; Damanik, Mariana Feronica; Rizky, Eky Muhammad (JURUSAN TEKNIK SIPIL, 2024)
The development of construction projects cannot be separated from project control management, one of which is construction cost management. In its implementation, there are many problems that cause cost overruns. The objectives of this research are to identify architectural work components that have the potential to be value engineered, to determine the difference in project costs before and after value engineering is applied, and to determine the project cost efficiency obtained after the application of value engineering. The research method used in this research is Value Engineering Work Plan which consists of information stage, function analysis stage, creative stage, evaluation stage, development stage, and recommendation stage. Life Cycle Cost (LCC) analysis and Analytical Hierarchy Process (AHP) method were used to determine the value of work efficiency. From the results of the research, it was found that walls, partitions, ceilings, and floors are architectural work items that can be applied to VE Analysis. The cost difference from the results of replacing the initial design with the recommended design, obtained a total cost savings of Rp 2.454.714.553,78 from the total cost of architectural work of Rp 11.178.625.221,13.